Innovative dual storage heat tank combination solar thermal, air conditioners and heat pump of water heating systems - Wen, Lih Chen; King, Leung Wong; Yung, Chang Li (Universiti Kebangsaan Malaysia, 2015)
Tropical or subtropical countries are very suitable for the development of solar and heat pump technology. This paper proposed the integration of air conditioners that exhaust heat with solar energy to enhance the overall efficiency of thermal energy conversion. The analysis of thermal storage tanks of different volumes showed that a two-ton air conditioner operating for an hour produced double energy than normal sunshine for a day. With thermal storage tanks of fixed volume, the integration of air conditioners of different tons with solar energy indicated that air conditioners of less tons produced faster and more efficient energy conversion. Therefore, this paper proposed that the modification of condenser in domestic air conditioner into water-cooled condenser not only enhance the energy efficiency of air conditioners but also increased hot water supplies since hot water from air conditioners could be integrated into solar water heaters. By doing so, energy conservation and carbon reduction could be achieved.